Pathogenesis and therapeutic intervention of oral submucous fibrosis - Thukanaykanpalayam Ragunathan Yoithapprabhunath; Thangadurai Maheswaran; Janardhanam Dineshshankar; Abraham Anusushanth; Pandian Sindhuja; Govindasamy Sitra (Wolters Kluwer Medknow Publications, 2013)
Oral submucous fibrosis (OSF) is a chronic, progressive, potentially malignant condition affecting the oral cavity and frequently involving the upper part of the aerodigestive tract including the oropharynx and the upper part of the esophagus. It is characterized by juxtaepithelial inflammatory reaction and progressive fibrosis of lamina propria, leading to stiffening of the oral mucosa eventually causing trismus. This condition is associated with significant morbidity and high risk of malignancy. Over the years, several drugs and combinations have been tried for the treatment of submucous fibrosis, but with limited success, because of its unclear molecular pathogenesis. Till date, there are no known effective treatments for OSF. The aim of this article is to emphasize on the molecular changes taking place in OSF and possible therapeutic interventions.